2020
DOI: 10.1111/sode.12496
|View full text |Cite
|
Sign up to set email alerts
|

The structure of emotion regulation strategies in adolescence: Differential links to internalizing and externalizing problems

Abstract: Emotion regulation is a multi-modal construct, that includes both adaptive and maladaptive cognitive-behavioral processes. However, many classifications of regulation strategies do not take this multi-modality into account.In this study, two classification systems were integrated.Participants were 336 adolescents (56% boys, M age = 15.41, SD = 1.45). Anger regulation strategies were measured with a questionnaire that assessed general strategies, and a vignette measure that assessed contextual strategies.Confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 67 publications
(92 reference statements)
1
14
0
Order By: Relevance
“…These families of functional strategies represent behavioral rather than cognitive ER. Interestingly, one study that analyzed profiles of dysfunctional ER also found externalizing problems to be associated with a more behavioral regulation style, whereas a cognitive regulation style was more strongly related to internalizing problems ( 65 ). The findings of our study extend these results with regard to functional ER and suggest that this distinction may also be useful for future research.…”
Section: Discussionmentioning
confidence: 99%
“…These families of functional strategies represent behavioral rather than cognitive ER. Interestingly, one study that analyzed profiles of dysfunctional ER also found externalizing problems to be associated with a more behavioral regulation style, whereas a cognitive regulation style was more strongly related to internalizing problems ( 65 ). The findings of our study extend these results with regard to functional ER and suggest that this distinction may also be useful for future research.…”
Section: Discussionmentioning
confidence: 99%
“…However emotion regulation strategies usually work in concert (Ford et al, 2019). Accordingly, recent studies on emotion regulation in children and adolescence started focusing on profiles of emotion regulation strategies (e.g., te Brinke et al, 2020; van den Heuvel et al, 2020; Zhang et al, 2019). These type of investigations cluster participants into separate groups according to similar emotion regulation profiles.…”
Section: The Development Of Self-conceptmentioning
confidence: 99%
“…On the other hand, the vulnerability‐stress model of psychopathology proposes that individuals who engage in behavioral problems may likely share vulnerability factors (e.g., impulsive and aggressive traits, high aversive emotions), and adolescents with these vulnerability factors are at a higher risk of subsequent adjustment problems, such as NSSI or suicide attempts (Hayes et al, 1996; Marsh et al, 2009; Nock, 2010). Besides, adolescents with behavioral problems report more intense emotions and high degrees of behavioral maladaptive emotion regulation strategies (te Brinke et al, 2020), for these young people, NSSI may be an effective means of diminishing aversive symptoms by regulating these emotions (Cassels et al, 2019).…”
Section: Introductionmentioning
confidence: 99%